Improved semen parameters and sperm deoxyribonucleic acid fragmentation following microscopic varicocelectomy: short term results of a prospective study - Nagabhaiarav, Manu K.; Meyyappan, Vivek; Thimmegowda, Manasa; Javali, Tarun; Rao, Gopal K. S. (International Surgery Journal, 2024)
Background: Assessment of sperm deoxyribonucleic acid (DNA) damage post varicocelectomy, has brought about new prospects in treating men with infertility. Improvements in spermatogenesis with decrease in sperm DNA damage has been demonstrated which has led to significant enhancement in fertility rates. Therefore, we evaluated the efficacy of microscopic varicocelectomy on the reduction in sperm DNA damage in concurrence to the conventional improvement of semen parameters. Methods: All patients with a diagnosis of varicocele leading to infertility and planned for microscopic varicocelectomy from January 2013 through September 2019, were included in the study. Sperm chromatin structure assay (SCSA) was done preoperatively and at 3 and 6 months postoperatively for sperm DNA integrity assessment and the results expressed as sperm percentage DFI were compared. A p value <0.05 was considered statistically significant. Results: 105 infertile men underwent microscopic varicocelectomy. Mean age and infertility period from the date of unprotected sex were 26.5±5.6 years and 30 months respectively. Baseline mean sperm concentration was 29 million/ml, mean progressive motility 24% and a percentage DFI ranged from 5–36% with a mean of 16%. Sperm DNA integrity improved significantly with a DFI decrease from 25±11% to 18±6%, 3 months post-surgery which was consistent at 6 months (13±5%). Sperm concentration and progressive motility increased with a mean sperm count improvement by 21.9 million/ml and mean motility by 20.3%. Conclusions: Microscopic varicocelectomy provides durable improvement in DNA integrity and semen parameters. Sperm DNA integrity assessment using SCSA is a useful tool to demonstrate change in the semen quality post treatment.